Analisis Faktor-Faktor yang Mempengaruhi Penurunan Penjualan Manis Jaya Fotokopi di Karanganyar - Eni Sri Lestari; Ari Susanti (Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the factors influencing the decline in sales at Manis Jaya Fotokopi Karanganyar, focusing on promotional strategies, operating hours, and human resources. The study used a quantitative approach with a sample of 97 respondents. Validity and reliability tests showed that all research instruments were valid and reliable. Classical assumption tests demonstrated that the data were normally distributed, free from multicollinearity, and free from heteroscedasticity. Multiple linear regression analysis found that promotional strategies, operating hours, and human resources significantly influenced the decline in sales. A simultaneous test (F-test) showed that all three independent variables collectively contributed significantly to the decline in sales, contributing 78.6% according to the Adjusted R-squared value. These findings indicate that improving promotional strategies, adjusting operating hours, and strengthening human resources are strategic steps to increase sales volume.